Experimental and theoretical study on static recrystallization of a low-density ferritic steel containing 4 mass% aluminum. (15th October 2019) - Xu, Xiangyu; Li, Jianzhe; Li, Weijie; Liu, Qiannan; Liu, Dan; Wang, Xuemin; Wang, Jingliang; Shang, Chengjia; Misra, R.D.K.
Abstract: The static recrystallization behavior of a low-density δ-ferritic steel containing 4 wt% Al was investigated by means of hot compression tests. The fractional softening obtained from the interrupted hot compression tests was used as a measure of the combined effect of static recovery and recrystallization. The single-pass hot compression tests followed by holding were performed to reveal the degree of static recrystallization. The experimental results indicated that the onset of static recrystallization occurred at a fractional softening of 0.6, which was lower than that of other ferritic steels. Moreover, the nucleation of recrystallization was dominated by strain induced grain boundary migration. First-principles calculations were performed to verify the effect of Al on recovery, which was influenced by stacking fault energy. It was found that the stacking fault energy of the steel is 105 mJ/m 2, much lower than that of pure iron, which explained the suppressed recovery and correspondingly the promoted recrystallization. Based on the experimental results, a new multi-pass hot rolling process with on-line annealing was developed. The grain size of the low-density δ-ferritic steel was refined to 85 μm by static recrystallization and the mechanical properties can meet the requirement for hull steels. Highlights: Static recrystallization of the experimental steel occurred when a minimum fractional softening value of 0.6 was achieved. The relationship between fractional softening and recrystallization fraction can be expressed as a quadratic relationship. The main nucleation mechanism of static recrystallization was determined to be strain induced grain boundary migration. Al decreases the stacking fault energy of ferrite, which suppressed recovery and correspondingly promoted recrystallization.